The Effects of Respondents' Consent to Be Recorded on Interview Length and Data Quality in a National Panel Study. Issue 4 (November 2015) - McGonagle, Katherine A.; Brown, Charles; Schoeni, Robert F.
Recording interviews is a key feature of quality control protocols for most survey organizations. We examine the effects on interview length and data quality of a new protocol adopted by a national panel study. The protocol recorded a randomly chosen one-third of all interviews digitally, although all respondents were asked for permission to record their interview and interviewers were blind as to whether or not interviews were recorded. We find that the recording software slowed the interview slightly. Interviewer knowledge that the interview may be recorded improved data quality, but this knowledge also increased the length of the interview. Interviewers with higher education and performance ratings were less reactive to the new recording protocol. Survey managers may face a trade-off between higher data quality and longer interviews when determining recording protocols.